Experimental study on the bearing capacity of PZ shape composite dowel shear connectors with elliptical holes - Huang, Pingming; He, Junlong; Kong, Fanlei; Mei, Kuihua; Li, Xiaolong (Scientific reports, 2022)
The push-out test was carried out in order to study the shear performance of perfobond ribs (PBL) and puzzle (PZ) shape composite dowel shear connectors which are used in corrugated steel–concrete composite bridge decks. By considering the influencing factors of transversal reinforcement, elliptical holes and bonding friction forces, eight specimens were designed and prepared. The load–slip curves were obtained, and the static mechanical properties, including bearing capacity, slip, shear stiffness, and ductility factor, were analyzed. The formula of bearing capacity and load–slip curve were proposed. The results showed a clear deformation of the transversal reinforcement of both the two types of shear connectors. The dominating failure mode of both the shear connectors was the double plane shearing of the concrete dowel. The load–slip curves of the two types of shear connectors followed the same trend. The PZ shape composite dowel performed better in ultimate bearing capacity, ductility, and shear stiffness than the PBL shear connector. Elliptical holes in a PZ shape composite dowel significantly increased the ultimate bearing capacity. The shear stiffness increased with transversal reinforcement and reduced with elliptical holes. For PBL shear connectors, the strain change in the C1 area near the loading point was most apparent. While, the A1 and B1 areas were stress concentration locations for PZ shape composite dowel shear connectors. The two formulas were in good agreement with the test results.